Ruptured Cerebral Aneurysms and Dissecting Aneurysms in Patients with COVID-19: A Case Series and Literature Review - Wajima, Daisuke; Shimozato, Rin; Takeshita, Tomonori; Nagamine, Tomoaki (Indian Journal of Neurosurgery, 2023)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been associated with a hypercoagulable state and ischemic stroke. However, aneurysmal subarachnoid hemorrhage (SAH) due to SARS-CoV-2 infection is uncommon. Here, we report a case series of SAH caused by ruptured cerebral aneurysms or dissecting aneurysms (DAs) in patients with coronavirus disease 2019 (COVID-19) and discuss the potential relationships between them.Case Description Four of the six patients had a history of COVID-19, ranging from 2 to 9 days, one had COVID-19 pneumonia for 1 month, and one had SARS-CoV-2 positivity on admission. Plain head computed tomography revealed diffuse SAH in all cases, while angiography revealed a DA in the right posterior cerebral artery (P2 portion) in patient 1, DA in the right vertebral artery (VA) in patients 2 and 6, anterior communicating artery aneurysm in patient 3, blister aneurysm in the right internal cerebral artery (ICA) (C2 portion) in patient 4, and DAs in the right VA and extracranial portion of the right ICA in patient 5. Treatment comprised internal trapping for patients 1, 2, and 6; neck clipping for patient 3; stent-assisted coiling for patient 4; and internal trapping and flow diversion for patient 5. All the patients' postoperative courses were uneventful.Conclusion The present cases alone do not provide clear evidence on whether SARS-CoV-2 infection causes ruptured cerebral aneurysms or DAs. Therefore, accumulation of more cases and further studies are needed to clarify the relationship between SARS-CoV-2 infection and these aneurysm conditions.
Keywords: angiography; COVID-19; intracranial aneurysms; ischemic stroke; SARS-CoV-2; subarachnoid hemorrhage